Media Sosial Instagram Sebagai Media Edukatif Dalam Bingkai Sosiologi Pendidikan - Kurniawati, Atik; Fitri , Meila Riskia; Kabelen, Marista Christina Shally (Prodi Sosiologi Universitas Mataram, 2024)
This research aims to discuss the social media Instagram as an educational medium through the perspective of Sociology of Education. Specifically, it aims to, first, find out the main components of Instagram social media, second, to find out the role of actors and third, analyze educational accounts from the perspective of the sociology of education. The research method used is descriptive qualitative with interviews and observations related to educational accounts. The subjects of this research are 8 owners of educational accounts on the social media Instagram, namely @kokbisa, @mudanerdaya.id, @socialkreatif, @folkative, @asumsico, @karirlab, @mamanbasyaiban, @cepatpede.academy. The research was conducted from May 2024 to October 2024. The concepts used in this research were social media, Instagram, and education using an educational sociology perspective. The result of this research is that we can find out the 4 components of Instagram social media which include context, communication, collaboration and connection. Second, optimize the role of actors as policy makers, coordinators, facilitators, implementers and accelerators. Third, analyze Instagram social media as a